Comparative nest survival of three sympatric loon species breeding in the Arctic. (18th July 2018) - Uher‐Koch, Brian D.; Koch, Joshua C.; Wright, Kenneth G.; Schmutz, Joel A.
Abstract : Identifying factors influencing nest survival among sympatric species is important for understanding and managing sources of variation in population dynamics of individual species. Three species of loons nest sympatrically in northern Alaska and differ in body size, life history characteristics, and population trends. We tested the effects of competition, nest site selection, and water level variations on nest survival of Pacific Gavia pacifica, yellow‐billed G. adamsii, and red‐throated loons G. stellata on the Arctic Coastal Plain in Alaska. Although overall nest survival rates did not differ between species, the factors influencing nest survival varied. Nest site selection influenced nest survival for Pacific and yellow‐billed loons, with both species having high nest survival when nesting on islands and peninsulas, likely due to a reduction in access by terrestrial predators. However, on mainland shorelines, Pacific loons had lower nest survival than yellow‐billed loons, and used a higher proportion of vegetation mats for nest sites suggesting that their smaller body size makes them less adept at nest defense. Nest site selection did not influence nest survival of red‐throated loons corresponding to our result of no nest site preferences by this species. Initiation date had a strong influence on nest survival for Pacific and yellow‐billed loons with nests laid earlier having higher survival. Pacific and yellow‐billed loon nests were susceptible to flooding due to precipitation, which contrasted with red‐throated loons that nest on smaller lakes with lower water level variations. Competition did not affect nest survival for any of the species likely due to most territorial encounters occurring prior to incubation. The only influence we found on red‐throated loon nest survival was differences among years. Our results indicate that loons chose nest sites based on predation risk and that factors influencing breeding success of closely related species may differ under similar breeding conditions.